2000
DOI: 10.2307/2656734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pollen load size and source (self, outcross) on seed and fruit production in highbush blueberry cv. ‘Bluecrop’ (VACCINIUM CORYMBOSUM; Ericaceae)

Abstract: Reproductive fitness of a plant is ultimately determined by both number and quality of seed offspring. This is determined by sexual selection of pollen microspores and ovules during pollination and fertilization. These processes may include pollen competition and seed abortion, which reduce the number of microspores and ovules available for final seed production. Thus, even an excess of pollen microspores to ovules does not result in fertile seeds equal to ovule number. We investigated pollen requirements of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 59 publications
2
93
0
7
Order By: Relevance
“…The smaller seed set produced as a consequence of male compared to female visits may directly result from their smaller pollen load (Marshall et al 2000;Dogterom et al 2000). It may also reflect different sex-specific behaviour.…”
Section: Discussionmentioning
confidence: 98%
“…The smaller seed set produced as a consequence of male compared to female visits may directly result from their smaller pollen load (Marshall et al 2000;Dogterom et al 2000). It may also reflect different sex-specific behaviour.…”
Section: Discussionmentioning
confidence: 98%
“…3A). Measuring this downstream outcome variable is important, because pollen deposition does not necessarily lead to fruit set (61) [e.g., if pollinator visits are at saturating levels and result in flower damage or the transfer of poor quality/incompatible pollen (62,63)]. For example, in our study, honey bees were good at depositing pollen in many crops, but increased honey bee visitation did not increase fruit set, a result that other researchers (11, 64) also have found.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, higher but not excessive numbers of pollen grains and beneficial for optimal seed and fruit production since pollen competition, ovule and seed abortion, pollen tube attrition and physical blockage of pollen grains limit the number of successful fertilisations and seed set (Dogterome et al, 2000). Wachira and Kamunya (2005) found that the cross and self pollen tubes of tea grow at different rates and compete to fertilise the ovule.…”
Section: Introductionmentioning
confidence: 99%